A PALYNOLOGICAL STUDY OF THE SAWAHLUNTO FORMATION OMBILIN BASIN, WEST SUMATRA - Katherine M. Bartram; Lucilla Nugrahaningsih (Testing Center for Oil and Gas LEMIGAS, 1990)
Low to moderate yields of well preserved Palunomorphs were recovered from the Sawahlunto Formation, Ombilin Basin, West Sumatra. More than 50 spore-pollen species have been recognised of which many have been corroborated with previously described taxa. The palynological assemblages recovered indicate an Oligocene to lower Miocener rather than Eocene age for the deposition of the Sawahlunto Formation.